Design and validation of the “dimensions of forced labour” measurement scale - Farias Montemayor, Oscar Mario (2025)
Forced labour is a serious form of labor exploitation that affects fundamental human and socioeconomic rights, characterized by practices of coercion, abuse and deception. This study aimed to design and validate a measurement scale that allows evaluating the key dimensions of forced labor, based on the indicators established by the International Labor Organization (ILO). The research included an exhaustive literature review, consultations with experts in labor law and the application of the instrument to a pilot sample of 150 people, later expanded to 300 participants in Coahuila, Mexico. The results of the exploratory factor analysis identified 10 main dimensions, which explained 68.5% of the total variance. These dimensions encompass explicit coercion, abusive working conditions, restriction of movement, isolation, specific vulnerabilities, economic servitude, interpersonal violence, and deception. The scale proved to be reliable, with an initial Cronbach's alpha of 0.908 and a final one of 0.863. This instrument is presented as a validated tool that facilitates the identification and analysis of forced labor, contributing to the identification of the multiple manifestations of this global phenomenon.